ACCOMMODATIVE INSUFFICIENCY MANAGEMENT: DOES +2.00D ADD WORK FOR ALL? - Tengku Abdul Aziz , Tengku Aida; Che Abdullah , Najmah; Hanaffi , Nurmizan; Mohd Yusof , Nor Fadilawati; Waheeda-Azwa, Hussein; Md-Muziman-Syah, Md Mustafa (International Journal of Allied Health Sciences, 2021)
Maximum addition (ADD) of +2.00D has commonly suggested management for accommodative insufficiency (AI) in ophthalmic literatures. Interesting to be described in this case report, a severe AI associated with convergence insufficiency requires higher ADD than +2.00D. A 27-year female presented with blurry vision, diplopia and eyestrain during near work, and the symptoms are worsening since age of 10. The distance and near visual acuity were 6/6 and N24 respectively, in either eye. The monocular and binocular amplitude of accommodation were 1.00D with -0.50D relative accommodation, 30cm near point of convergence (NPC), 14pd near and 2pd distance phoria (Maddox test), and 14pd near positive fusional vergence. With the prescription of +3.00D ADD, letter “E” push-up and dot-card therapy, the reported- symptoms were alleviated as well as the accommodative and vergence systems improved after a month. This case report presents that the treatment approach works for severe AI with remote NPC. Therefore, it is suggested as initial management prior to further therapy. Keywords: severe accommodative insufficiency, convergence insufficiency, management